Reduced expression of the retinoblastoma protein shows that the related signaling pathway is essential for mediating the antineoplastic activity of erufosine. - Maya M Zaharieva (Public Library of Science (PLoS), 2014)
Erufosine is a new antineoplastic agent of the group of alkylphosphocholines, which interferes with signal transduction and induces apoptosis in various leukemic and tumor cell lines. The present study was designed to examine for the first time the mechanism of resistance to erufosine in malignant cells with permanently reduced expression of the retinoblastoma (Rb) protein. Bearing in mind the high number of malignancies with reduced level of this tumor-suppressor, this investigation was deemed important for using erufosine, alone or in combination, in patients with compromised RB1 gene expression. For this purpose, clones of the leukemic T-cell line SKW-3 were used, which had been engineered to constantly express differently low Rb levels. The alkylphosphocholine induced apoptosis, stimulated the expression of the cyclin dependent kinase inhibitor p27Kip1 and inhibited the synthesis of cyclin D3, thereby causing a G2 phase cell cycle arrest and death of cells with wild type Rb expression. In contrast, Rb-deficiency impeded the changes induced by erufosine in the expression of these proteins and abrogated the induction of G2 arrest, which was correlated with reduced antiproliferative and anticlonogenic activities of the compound. In conclusion, analysis of our results showed for the first time that the Rb signaling pathway is essential for mediating the antineoplastic activity of erufosine and its efficacy in patients with malignant diseases may be predicted by determining the Rb status.